Assessing the effects of inspiratory muscle training in a patient with unilateral diaphragm dysfunction - Mayra Caleffi Pereira (2019)
© ERS 2019. A 55-year-old man was referred to the outpatient pulmonary department of our hospital because of dyspnoea during exertion and when bending forward, which had been present for at least 6 months. He reported experiencing severe symptoms of breathlessness and many of his daily activities had to be adapted or interrupt due to symptoms (as documented by the Baseline Dyspnea Index (BDI)) (table 1). Recent infectious episodes or episodes of neck or shoulder pain were absent. His medical history included systemic arterial hypertension, obesity (body mass index (BMI) 36 kg·m−2), and obstructive sleep apnoea for which he was treated with night-time continuous positive airway pressure therapy (8 cmH2O). He was a former smoker (18 pack-years) who quit smoking 15 years ago. 8 months ago, he underwent abdominal surgery (transabdominal epigastric hernia repair). The presence of cardiopulmonary disease and other aetiologies, such as neuromuscular disease, was excluded. Chest radiograph showed an elevated left hemidiaphragm and impaired left phrenic nerve conduction (i.e. increased latency and compound muscle action potential (CMAP) duration) after electrical stimulation (table 1) [1].